Courland Pt., Tobago - (:unkn) unknown (My University, 2011)
The postcard shows birds circling to nest on a rocky piece of land on Courland Point, a point south of Plymouth on Tobago's west coast.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Beaches--Trinidad and Tobago; Birds--Trinidad and Tobago; Capes (Coasts)--Trinidad and Tobago